IMPLEMENTASI PENGUKURAN KAPABILITAS TATA KELOLA TI MENGGUNAKAN COBIT 5 - Ahmad Faruq; Indri Sudanawati Rozas; Noor Wahyudi (Universitas Methodist Indonesia, 2023)
Information technology (IT) is crucial for organizations to gain profits, maximize time and minimize costs. Dinas XYZ is a government agency located in East Java, aware of this and implementing IT in their daily operations. Because of this, measurement of IT governance is needed to determine the extent to which IT supports the operational activities of the XYZ Agency. There are 9 domains selected to determine the level of capability. The result is that seven domains are at level 2 namely lAPO01, lAPO02, lAPO04, lAPO08, lAPO10, lBAI02, and lDSS02. While the two domains, namely BAI01 and EDM02, are at level 1. The capability value obtained is 1.7, while the desired level is level 3. Therefore, there is a gap of 1.3. The XYZ Service can improve the level obtained to the desired level by implementing the recommendations provided.